Three translations of Hedda Gabler - Nelson, Lois G. (My University, 1972)
The three translations of Henrik Ibsen's Hedda Gabler done by William Archer in 1891, Eva LeGallienne in 1928, and Michael Meyer in 1960, revealed significant verbal differences. There were differences owing to the change in language with time, differences in English and American usage, differences in the way French expressions were used to indicate sophistication, and differences in the ways of indicating degrees of intimacy between the characters.
Keywords: Ibsen, Henrik, 1828-1906 -- Translations; Ibsen, Henrik, 1828 - 1906 Hedda Gabler